Government Policy Overview of the Total Unemployment Rate in East Java 2001-2021: Evidence Vector Error Correction Model Approach - Sahril Kamal; Lutfi Asnan Qodri (Gorontalo Development Review, 2022)
This article aims to provide a summary of local governments' strategies as well as long- and short-term perspectives on the effects of East Java Province's population growth rate and Human Development Index on unemployment. This article's technique involves analyzing the impact of the dependent variable on the independent variable using parametric quantitative methodologies. In order to see both the short- and long-term consequences, an analysis of the Vector Error Correction Model is employed as the analytical model. The findings indicate that the Human Development Index and population growth rate have a short-term negative impact on unemployment in the province of East Java. In contrast, population growth in East Java Province has a beneficial effect on the rise in unemployment when considered over the long term. The Millennial Job Center and other programs are a long-term answer to the problem of unemployment in the province of East Java